Mô hình đa bước - đa biến trung gian về sự chứng thực của người nổi tiếng đối với sự kiện: trường hợp nghiên cứu tại Việt Nam - Trần Thị Kim, Phương; Hồ Mai Thảo, Nhi; Mai Thị Phương, Uyên; Nguyễn Ngọc Uyển, Nhi; Nguyễn Thị Uyên, Nhi; Bùi Thị Hải, Đường; Trần Trung, Vinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study proposes a multiple-step multiple mediator model to examine how celebrity attachment influences event attendees’ intentions within the celebrity endorsement process under the moderating role of celebrity branding. The conceptual model and research hypotheses were each evaluated using CB-SEM. Both paper-based and online surveys were used to collect data from 759 Vietnamese respondents, aged 15 and above, who followed either domestic or international celebrities and were interested in various events taking place in Vietnam. The results confirmed the cognitive, affective, and hybrid cognitive-affective pathways linking celebrity brand co-creation, celebrity attachment, and event participation intentions. Some practical implications have been suggested to celebrities and event managers to increase the effectiveness of the endorsement process and increase event participation intentions.